Effect of protein secondary structures in mixed feedstuff detected by Fourier transform infrared spectroscopy on ruminal protein degradation kinetics - Dasen Liu; Yanfang Li; Guangliang Zhang; Peng Zhang; Penghua Wu; Shai Wang; Xiuxiu Wang (Czech Journal of Animal Science, 2017)
The objective of this study was to investigate the relationship between the protein secondary structure and the protein rumen degradation kinetics and the protein fractions of mixed feedstuffs of soybean meal with distillers dried grains with solubles (DDGS) at five mixed ratios (DDGS to soybean meal: 100 : 0, 70 : 30, 50 : 50, 30 : 70, 0 : 100). The Fourier transform infrared (FTIR) as a novel and cheap approach was used to detect the protein secondary structure, and the in situ nylon bag method was used to measure degradation kinetics of protein. Protein fractions were classified based on the Cornell net carbohydrate protein system. The results showed that (1) with the increasing soybean meal rate, the ruminal degraded protein and fractions of PB1 and PB2 were changed, (2) a higher α-helix to β-sheet ratio could result in a higher ruminally degraded protein, lower PB3 and PC, and higher PB1 and PB2 fractions in the feedstuff. So, mixing processing changed the feedstuff protein molecular structure spectral feature, which could influence the rumen degradation kinetics and protein fractions. It was inferred that protein degradation rate in mixed feedstuff can be measured by FTIR.